Dasatinib does not exacerbate dexamethasone‐induced osteonecrosis in murine models of acute lymphoblastic leukemia therapy. Issue 4 (5th December 2021) - Finch, Emily R.; Janke, Laura J.; Li, Lie; Payton, Monique A.; Jenkins, David A.; Crews, Kristine R.; Relling, Mary V.; Karol, Seth E.
Abstract: Introduction: There are clinical reports that the incorporation of dasatinib may increase the frequency of osteonecrosis in acute lymphoblastic leukemia (ALL) treatment regimens. No rigorous testing of this hypothesis is available to guide clinicians. Methods: We tested whether oral dasatinib increased the frequency of dexamethasone‐induced osteonecrosis in a murine model and tested its effects on dexamethasone's antileukemic efficacy in a murine BCR‐ABL + model of ALL. Results: Dasatinib did not change the frequency of osteonecrosis ( p = .99) nor of arteriopathy ( p = .36) in dexamethasone‐treated mice when given at dosages that achieved clinically relevant steady‐state dasatinib plasma concentrations of 53.1 ng/ml (95% CI: 43.5–57.3 ng/ml). These dasatinib exposures were not associated with increased dexamethasone plasma exposure in nonleukemia‐bearing mice. These same dosages were not associated with any decrement in antileukemic efficacy of dexamethasone in a responsive BCR‐ABL + model of ALL. Conclusions: Based on the results of our preclinical murine studies, we conclude that dasatinib is unlikely to increase the osteonecrotic effects of dexamethasone in ALL regimens.